Effect of Lean Systematic Method on Specimen Handling Activities for Patients in Medical Wards - Bakar, Noor Widasuria Abu; Mohamad, Abdul Hadi; Jatavakabhulla, Pavan Kumar; Musa, Shahrulniza; Rahman, Marzilawati Abd; Soon, Lee Fat; Geek, Tan Seew; Rahim, Azahirafairud Abdul (International Journal of Engineering and Technology, 2018)
Lean is a quality improvement methodology that can identify and eliminate waste from processes. While the methodology is widely implemented in manufacturing and automotive, it is also applicable to another area such as the service industry of healthcare. Institutions who concern with health, such as the hospital involve complicated and lengthy business process daily. Consequently, this encourages the exhaustive process chain, which is unreliable, cost ineffective and resource wastage. Moreover, the chain may lead to medication error or error in medication delivery. Although the Lean systematic method is widely used in healthcare, there is limited empirical evidence in resolving such issues, mainly focusing on specimen handling in a real hospital environment. This paper generally focuses on the implementation of a systematic method of Lean into a healthcare institution in Malaysia to decrease the time access and to have better inventory control of specimen. The adoption of Lean is achieved by implementing an efficient barcode system namely Specimen Labelling System (SPLS) for specimen handling to pursue better management, which will lead to time reduction and allow the hospital to offer good quality healthcare service. The study confirms that the systematic Lean method is significantly improved actions and processes. The finding is also applicable to lead to a general patient satisfaction by adding values to the existing process but shorten some additional activities.